The Relationship between Nutritional Adequacy and Physical Activity with the Menstrual Cycle in Adolescents - Salsa Afidatur Risqo; Laksmi Maharani (Lembaga Pengembangan Kinerja Dosen, 2026)
Menstrual cycle disorders are still common in adolescent girls and can be influenced by various factors, including nutritional adequacy and physical activity. During adolescence, an imbalanced nutritional intake and inadequate physical activity can disrupt reproductive hormone regulation, potentially leading to menstrual irregularities. This study aims to determine the relationship between nutritional adequacy and physical activity and menstrual cycle disorders in adolescent girls. This study used a cross-sectional design involving 78 female adolescents aged 15–19 at SMKN 52 Jakarta, selected using a simple random sampling technique. Nutritional adequacy was assessed through a 24-hour food recall and classified based on the percentage of the Recommended Intake (RDA). Physical activity was assessed using the Physical Activity Questionnaire for Adolescents (PAQ-A). Menstrual cycle disorders were determined based on the average length of menstrual cycles over the past three months. Data analysis was performed using the chi-square test with a p-value <0.05. Most respondents had adequate nutritional intake (53.8%), while the majority demonstrated low levels of physical activity (57.7%). Abnormal menstrual cycles were reported by 56.4% of respondents. Bivariate analysis showed significant associations between nutritional adequacy and menstrual cycle patterns (p = 0.009), as well as between physical activity and menstrual cycle patterns (p = 0.001). In conclusion, nutritional adequacy and physical activity are associated with menstrual cycle among adolescent girls. Therefore, adequate nutritional intake and balanced physical activity should be considered important factors in maintaining regular menstrual cycles in adolescents.